Ti(OiPr)4-mediated multicomponent reactions involving triple additions to isonitrile carbon atoms - Foschi, Francesco; Roth, Torsten; Wadepohl, Hubert; Gade, Lutz H. (Organic letters, 2016)
Double addition of Grignard reagents to isonitriles was achieved in the presence of stoichiometric amounts of [Ti(OiPr)4]. Functionalized isonitrile components were obtained in situ via lithiation of chiral and achiral 2-oxazolines, and the resulting amidomethyltitanium intermediate further reacted with a range of electrophiles. The established multicomponent procedure gave rise to highly substituted 2-aminomorpholines, acyclic diamino alcohols, and prenylated amino alcohols via straightforward synthetic protocols.
Im Titel ist die Ziffer "4" tiefgestellt
Gesehen am 19.06.2020